W ZDETERMINOWANYM ŚWIECIE. O STOICKIEJ SILE RZĄDZĄCEJ KOSMOSEM - Wiśniewski, Hubert (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Is human life is determinated? On this question I try to answer through the analysis of the Stoic philosophy. The Stoics believed that whole world, including God, is material substance, and every thing has a particle of God. The cosmos is the result of the action of God and exists from one fire to the next. God is the active principle which is understood as Providence (pro,noia) and Fate (ei`marme,nh), and He takes care of the world and directs from the inside. However, there is a difference between Providence and Fate. Divine providence is a power – God extends the providence to the whole world, but fate is a chain of causes.